Prevalence of occupational health hazards and preventive measures applied by the workers of Shikhar Plywood Factory in Kharpu, Panauti in 2013. - Shrestha, Ankita (2014)
ABSTRACT: Occupational hazards are the situation that posses a level of threat to life, health, property or environment. Nepal has estimated that each year approximately 20,000 workers meet accidents at work place which lead to about 200 lives lost in Nepal. Risks of accidents and diseases are higher in all kinds of production processes where man, machine and materials are involved. A study entitled "Prevalence of Occupational Health Hazards and Preventive Measures Applied by the Workers of Shikhar Plywood Factory" was conducted to describe the prevalence and use of preventive measures regarding occupational health hazard among the workers of Shikhar plywood factory. The study was a quantitative, cross sectional study conducted to identify the prevalence of occupational health hazards, factors related to occupational health hazards and adoption of preventive measures by the workers in Shikhar plywood factory. A sample of hundred ten workers were interviewed by using purposive sampling method and with the help of a semi-structured questionnaire. The study variables were categorized as dependent and independent variables. The dependent variable was occupational health hazard and the independent variables were age, sex, level of education, work experience, work hours, lack of orientation on safety measures, supervision of working style and working situations, safety rules and regulations, provision of necessary safety equipments, loss of concentration on work. The statistical analysis like frequency and percentage tables performed for univariate analysis. Bivariate analysis was done by using chi square statistics. The major findings of study revealed that there was presence of occupational heath hazard with common form of hazard i.e. wood dust in Shikhar plywood factory. According to this study, there exist occupational health hazard among the young adults. The study showed that there was significant association between working hours and prevalence of occupational health hazard as well as significant association between working experience and prevalence of occupational health hazard. Similarly, with loss of concentration, there exist occupational health hazard. But there was no association between educational status and prevalence of occupational health hazard. Instead of provision of safety rules and regulations and supervision of working style and working situations there was prevalence of occupational health hazard in the factory. So, according to this research, there was increased in occupational health hazard with increasing working hours therefore strict duty hour should be maintained so that it will help to minimize the stress for those working for prolong hour. Instead of provision of rules and regulations, supervision, orientation there was increased hazard thus; implementation of policies like pre placement and ongoing training to the staff for the prevention of occupational health hazards and distribution of the safety measures for encouraging its compulsion use should be done which can be helpful for its prevention.